Instructional design approaches in genetics education: ADDIE versus differentiated instruction - Charles Kenneth Addo (International Journal of Mathematics and Sciences Education, 2025)
Genetics remains a conceptually challenging domain in senior high school biology in Ghana, as evidenced by persistently low student achievement despite ongoing curriculum reforms. These challenges are often attributed to teacher-centered instructional practices, large class sizes, and the limited use of pedagogical approaches that balance structure and flexibility. This study investigated the comparative effectiveness of two instructional frameworks: the structured, phase-based ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) and learner-centered Differentiated Instruction (DI). A quasi-experimental, non-equivalent pretest–posttest design was employed involving 120 senior high school students from two intact classes. One group was taught using the ADDIE model, while the other received instruction through DI strategies. Data were analyzed using descriptive statistics, independent samples t-tests, and two-way ANOVA. The findings revealed a statistically significant difference in posttest achievement, with students in the ADDIE group attaining higher mean scores (M = 28.92, SD = 3.84) than those in the DI group (M = 22.65, SD = 3.85), corresponding to a large effect size (Cohen’s d = 1.63). The two-way ANOVA indicated significant main effects of instructional model and gender, with male students outperforming female students overall, but no significant interaction effect between instructional model and gender. These results suggest that the systematic and iterative nature of the ADDIE model more effectively supports students’ understanding of complex genetics concepts in this context. The study recommends integrating the ADDIE framework into biology instruction while strategically incorporating differentiated strategies and gender-responsive practices to address learner diversity and promote equitable learning outcomes.